Updated species list of Cynipidae (Hymenoptera) from Turkey - Azmaz, Musa; Katilmiş, Yusuf (Zootaxa, 2017)
An updated species list of cynipids in Turkey and knowledge on their distribution and host plant/gall in the country are presented in this study. The present list has been based on previous studies in the literature and contains all reported cynipids from Turkey, including a new record (Andricus istvani Melika, 2008). In total, the Cynipidae in the Turkish fauna presently comprises 148 species in 25 genera and 9 tribes.